Why Pediatric Ethics Needs a Theory of Goodness - Tate, Tyler (The Hastings Center report, 2026)
We begin this commentary with a brief analysis of “Making Medical Decisions for Children with Profound Cognitive Disabilities: Pluralism and the Best Interest Standard,” by Pierce Randall, and “A Life Worth Sustaining? Bestowed Worth and Pediatric Care,” by Daniel T. Kim and Xiang Yu, in the same issue of the Hastings Center Report. These two articles examine decision-making for children with profound cognitive disabilities and critique the relational potential standard found in pediatric ethics. We agree with the authors that the relational potential standard risks using children as a means to other people's ends. We also raise two additional concerns: the standard is incongruent with parents’ self-descriptions, and it neglects the concept of goodness, which we take to be the fundamental concern of pediatric ethical analysis. We close with a brief discussion of goodness and consider how goodness might serve as the lodestar of pediatric ethics.